Coding roles of long non-coding RNAs in breast cancer: Emerging molecular diagnostic biomarkers and potential therapeutic targets with special reference to chemotherapy resistance - Kashyap, Dharambir; Sharma, Riya; Goel, Neelam; Buttar, Harpal S.; Garg, Vivek Kumar; Pal, Deeksha; Rajab, Khairan; Shaikh, Asadullah (Frontiers in Genetics, 2023)
Dysregulation of epigenetic control or modification in gene expression without any change in the nucleotide sequence of that gene has depicted severe pathological consequence in cancer development and progression. Several modes of epigenetic regulation, including DNA methylation (hypomethylation or hypermethylation of promotor), histone modifications (methylation or acetylation, etc.), abnormal expression of microRNAs (miRNAs), long non-coding RNAs, and small nucleolar RNAs, are not understood as yet. Emerging evidence suggests that lncRNAs exert pivot roles in all kinds of human cancers, including the breast cancer. LncRNAs with oncogenic and tumour suppressive potential exist and are reported to have an essential regulatory function in all breast cancer hallmarks. Differentially expressed lncRNAs contribute a remarkable role in the development of primary and acquired resistance for radiotherapy, endocrine therapy, immunotherapy, and targeted therapy. A wide range of molecular subtype specific lncRNAs have been assessed in breast cancer research. A number of studies have also shown that lncRNAs may be clinically used as non-invasive diagnostic biomarkers for early detection of breast cancer. Such molecular biomarkers have also been found in cancer stem cells of breast tumours. The objectives of the present review are to summarize the important roles of oncogenic and tumour suppressive lncRNAs for the early diagnosis of breast cancer, metastatic potential, and chemotherapy resistance.